The Influence of Alexithymia on the Tendency of Social Media Addiction in Early Adults in Karawang - Alifiany Indah Suciaty; Wina Lova Riza; Dinda Aisha (Eduvest - Journal of Universal Studies, 2024)
The internet offers numerous features that simplify activities like communication, information retrieval, and transactions, making social media increasingly accessible. In Indonesia, individuals in their productive years, particularly early adulthood, dominate internet usage. This phase is characterized by repetitive behaviors, which can escalate the intensity of social media use and potentially lead to addiction. One factor influencing this tendency is alexithymia. This study aims to explore the impact of alexithymia on social media addiction tendencies among early adults in Karawang. Employing a quantitative causality design, the research utilized non-probability sampling, specifically snowball sampling, to gather data from 385 respondents aged 20-30 years residing in Karawang. The Toronto Alexithymia Scale (TAS) was used to measure alexithymia, while the Bergen Social Media Addiction Scale (BSMAS) assessed social media addiction tendencies. Reliability was tested using Cronbach's Alpha, with a threshold of > 0.08, while normality was evaluated through the Kolmogorov-Smirnov test at a 5% significance level. Linearity was assessed using an ANOVA test, yielding a significance of 0.468 > 0.05. The results of the simple linear regression test showed a significance value of 0.000 < 0.05, confirming the hypothesis that alexithymia significantly influences social media addiction tendencies in early adulthood in Karawang. The determination test results indicated that alexithymia accounts for 54.2% of the variance in social media addiction tendencies (R-Square = 0.542), with the remaining 45.8% attributed to other variables not examined in this study.